2016
DOI: 10.4049/jimmunol.1601294
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Extrinsic TNF Collaborates with TRIF Signaling To Promote Yersinia-Induced Apoptosis

Abstract: Innate immune responses that are crucial for control of infection are often targeted by microbial pathogens. Blockade of NF-κB and MAPK signaling by the Yersinia virulence factor YopJ inhibits cytokine production by innate immune cells but also triggers cell death. This cell death requires RIPK1 kinase activity and caspase-8, which are engaged by TLR4 and the adaptor protein TRIF. Nevertheless, TLR4- and TRIF-deficient cells still undergo significant apoptosis, implicating TLR4/TRIF-independent pathways in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 52 publications
9
33
0
Order By: Relevance
“…Activation of TNFR, Fas and TNF‐related apoptosis‐inducing ligand receptors (TRAIL‐Rs or DR4/5) stimulates various downstream cell death pathways . However, only TNFR1 and Fas can induce downstream cell death pathways via RIPK1 . In recent years, researchers have found that TLRs can also activate downstream cell death pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of TNFR, Fas and TNF‐related apoptosis‐inducing ligand receptors (TRAIL‐Rs or DR4/5) stimulates various downstream cell death pathways . However, only TNFR1 and Fas can induce downstream cell death pathways via RIPK1 . In recent years, researchers have found that TLRs can also activate downstream cell death pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, another subtype of fibrinoid necrosis is represented by precipitated fibrinoid which is associated with immune complex diseases. 40 Pyroptosis might also play a role in caseating necrosis, as intracellular pathogens are classical inducers of the NLRP3 inflammasome 41 and also activate caspase-11, 42 both of which are required to control bacteria that escape the vacuole. Mechanistic insights into the pathophysiological relevance of these immune complex-triggered necrotic areas came from mice that are deficient in LC3-associated phagocytosis (LAP, a form of noncanonical autophagy 36 ).…”
Section: Morphological Aspects Of Necrosismentioning
confidence: 99%
“…The acetyltransferase YopJ (YopP in Y. enterocolitica ) is a homologue of Salmonella AvrA that inhibits transforming growth factor beta‐activated kinase 1 (TAK1), IκB kinase β (IKKβ) and mitogen‐activated protein kinase (MAPK) kinases, inhibiting pro‐inflammatory signalling in response to TLR and/or TNF signalling (Peterson et al, ; Pinaud et al, ). TAK1 inhibition promotes non‐canonical RIPK1‐FADD‐caspase‐8‐dependent GSDMD cleavage, pore formation and cell death in mouse macrophages.…”
Section: Yersinia Spp and Inflammasome Manipulationmentioning
confidence: 99%
“…The resulting potassium efflux triggers NLRP3 and caspase‐1 activation, and release of IL‐1β (Philip et al, ; Orning et al, ) (Figure f). In addition, blockade of TNF‐mediated pro‐survival NF‐κB and MAPK signalling by YopJ can also lead to RIPK1‐dependent apoptosis (Weng et al, ; Peterson et al, ; Peterson et al, ). Further, YopJ‐mediated inhibition of the Nod2 pathway has also been linked to Nod2‐dependent activation of caspase‐1 and IL‐1β release from Peyer's patches, and loss of intestinal barrier function in mice (Meinzer et al, ).…”
Section: Yersinia Spp and Inflammasome Manipulationmentioning
confidence: 99%
See 1 more Smart Citation